La couleur comme expérience synesthésique dans l’Antiquité - Mark Bradley (Mythos, 2017)
Colour is about more than just lightwaves hitting the retina. In ancient philosophical circles, colour was described as the primary object of vision: it was the external ‘skin’ that existed at the surface of an object, and what made the object visible or ‘sensible’ to a viewer. And yet, Greco-Roman literature is riddled with examples of colour categories that do not make sense simply in visual terms: from Homer’s ‘wine-dark sea’ (oinops pontos) to ‘whey-coloured’ (orōdēs) skin in Hippocratic medicine, from blushing (rubens) faces to the honey-coloured hair (mellei crines) and marbled skin of coveted girls in Augustan elegy, and from the saffron garments of decadent easterners to the expensive fishy-smelling purple robes of the late-antique imperial court, colours appealed not just to sight, but also to smell, touch and taste. This paper will use arguments and ideas explored in my monograph Colour and Meaning in Ancient Rome (Cambridge University Press, 2009) to suggest that colours in pre-modern societies such as Greece and Rome, because of their close ties to specific objects and phenomena (rather than just parts of the spectrum), were frequently synaesthetic experiences which appealed to multiple senses and mobilized more than just eyesight. I will draw upon case studies from a range of genres and contexts to demonstrate not only that colour was a multi-sensory experience, but also that the nature of this experience was a central preoccupation of ancient thought in several areas of activity in the Greco-Roman world. An understanding of this principle, then, can do more than just help us to translate and understand difficult Greek and Latin colour terms: colour was a basic sensory unit of information through which ancients experienced and evaluated the world around them, and the collaboration of the senses in these experiences suggests an approach to perception, knowledge and understanding which could be very different from that employed in the modern west.